Internship education analysis of vocational school students - POLAT, ZÜHAL; ÖZNAZ, DEMET; ULUSMAN, LEYLA; ORAL, BEKİR; ÇINAR, AYŞE; UZMANOĞLU, MUSTAFA SELÇUK; ACAR BÜYÜKPEHLİVAN, GÜLHAN; İŞGÖREN, AYŞE NURİYE (My University, 2010)
The main purpose of vocational and technical education is to make the individuals gain; knowledge, ability, and practice sufficiency which are needed for particular occupation. On the other hand the main function is to make the individual provide financial income and with this be useful to society at social and economic ways. Vocational and technical education has great affection power at development of country’s economy with human labor qualities. For this reason, in the developed countries vocational and technical education has special importance. In the developed countries; for more strong economy and more rapid social development, more qualified work labor is need to be provided. With this purpose, an effort is made to develop vocational and technical education. In Turkey, vocational schools are one of the most important education institutions at raising qualified human power. It is aimed the vocational school students to have more theoretical knowledge than technical man, and more practice ability than engineers by graduating with technician title. The cooperation between university and industry has importance at vocational school graduates having these abilities. In the education programs; students must continue a part of their education at industrial companies for 30 working days duration. This process is named as internship and it is necessary for the students to graduate. Students can find various abilities during the period where they were at the companies. In this study; it is aimed to analyze the expectations from internship education, and the gained knowledge and abilities of Marmara University Vocational School of Technical Sciences students. According to this, an answer is searched to the question “What kind of knowledge and abilities do the vocational school students gain during the internship period?” The universe of this study is the students studying at Marmara University Vocational School of Technical Sciences programs. It is goaled to discuss the education partnership between vocational school and industry according to the knowledge and abilities the students gained during the internship period.
Keywords: Sosyal ve Beşeri Bilimler; Social Sciences and Humanities; Sosyal Bilimler (SOC); Social Sciences (SOC); Vocational school; vocational education; internship; industry cooperation; vocational application